(untitled) (Global Journal of Science Frontier Research, 2021)
The basic structure of melatonin is evolutionarily conserved. Hence, it was speculated that melatonin may be present in different animals (from unicellular to multi-cellular) and even in plants. Melatonin in plans is generally regarded as phyto-melatonin. Like the role of melatonin in animals, phyto-melatonin can perform a number of functions like attenuation of apoptosis, prevention of free radical generation, protection against UV irradiation etc. But, unlike phytoestrogen, the role of phyto-melatonin in animals is totally an unexplored area. Hence, aim of the present study was to note the role of phyto-melatonin in maintenance of general health and immunity of goats. To fulfil the aim, we supplemented the goats with phyto-melatonin rich diet i.e. corn (Zea mays) which is having 1.4 ng/gm of dry weight of tissue and they are also edible to goats. We noted significantly high level of body weight, haematological (AST, ALT level, total RBC count and %Hb), immunological (TLC, %LC, %SR of PBMCs), metabolic (plasma glucose, cholesterol, HDL, LDL, protein levels and HDL: LDL ration), free radical (SOD, catalase, GPx levels), hormonal (estrogen, melatonin), cytokine (IL-6 and TNF-α) levels and significantly low level of MDA.